Interplay Between the Intestinal Microbiota and Acute Graft-Versus-Host Disease: Experimental Evidence and Clinical Significance - Hong, Tao; Wang, Rui; Wang, Xiaoqi; Yang, Shijie; Wang, Weihao; Gao, Qiangguo; Zhang, Xi (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative therapy for many hematological disorders and autoimmune diseases, but acute graft-versus-host disease (aGVHD) has remained a major obstacle that limits allo-HSCT and exhibits a daunting mortality rate. The gastrointestinal system is among the most common sites affected by aGVHD. Experimental advances in the field of intestinal microbiota research enhanced our understanding - not only of the quantity and diversity of intestinal microbiota - but also their association with homeostasis of the immune system and disease pathogenesis, including that of aGVHD. Meanwhile, ever-growing clinical evidence suggest that the intestinal microbiota is dysregulated in patients who develop aGVHD and that the imbalance may affect clinical outcomes, indicating a potential predictive role for microbiota dysregulation in aGVHD severity and prognosis. The current animal and human studies investigating the intestinal microbiota in aGVHD and the understanding of the influence and management of the microbiota in the clinic are reviewed herein. Taken together, monitoring and remodeling the intestinal microecology following allo-HSCT may provide us with promising avenues for diagnosing, preventing or treating aGVHD in the clinic.